Pengaruh Ekuitas Merek Terhadap Kepuasan Pelanggan Smartphone Merek Samsung Di Surakarta (Studi Empiris Mahasiswa FEB UMS) - Astuti Kurniawati, Sri, Drs. Wiyadi, MM, Ph.D (2017)
This study aims to determine the effect of variable Brand Loyalty, Perceived Quality, Brand Awareness and Brand Association on Brand Samsung Smartphone Customer Satisfaction in Surakarta on FEB students UMS. This study uses the survey design, the research took samples from a population and using questionnaires. Samples taken in this study were respondents who use a smartphone Samsung brands. Number of questionnaires in this research were 100 respondents FEB UMS Students were taken by purposive sampling. The analytical tool used in the research is to test the instrument, classic assumption test, data analysis (Multiple Linear Regression Analysis, t-test, F-tes and coefficient of determination (R²). Hypothesis tests showed the effect of variable Brand Loyalty, Perceived Quality, Brand Awareness and Brand Association have a positive and significant impact with t respectively 2,183, 2,590, 5,550 and 2,430. In the F test shows that jointly variables Brand Loyalty, Perceived Quality, Brand Awareness and Association Brand positive and significant impact on satisfaction customers with a probability value of 0,000 (0,000 < 0,05). And the coefficient of determination (R2) of 55,8%.